The Influence of Moral Choices in Video Games on Real-World Decision-Making and Empathy - Wang, Bangqiao; Wu, Youyou; Xu, Zirui (Transactions on Computer Science and Intelligent Systems Research, 2025)
This paper explores the impact of moral choices in video games on players’ real-world decision-making and ethical behavior. This study highlights the psychological benefits of engaging with morally complex decisions, while video games are often criticized for promoting violence and addiction. By analyzing some typical video game instances such as Detroit: Become Human, Red Dead Redemption 2, and The Last of Us Part II, the research shows how game decisions can enhance substitution, empathy, and moral reasoning. This study is conducted on data gathered from surveys and interviews with players of this kind of video game. In addition, thematic analysis and literature review better analysis of this data. This study demonstrates that moral choice mechanics in video games, such as Non-Player Character (NPC) feedback and morality meters, can influence players’ emotional engagement and ethical reasoning, potentially affecting real-world decision-making. However, this influence is complex and shaped by individual psychology, social context, and personal values, and there is a need for further research into long-term behavioral impacts. This research provides valuable implications for game developers, educators, and psychologists in designing interactive systems that promote ethical thinking.